(untitled) (World Economics and Finance Bulletin, 2025)
Unlike most previous research investigated the impact of tax policy on SMEs’ growth. However, this study investigates the differential effect of three components of the tax policy on the growth of SMEs in Iraq. Furthermore, the study is enhanced by incorporating tax compliance as a moderator. Panel Data were collected from 257 SME owners who have been registered for the past three years and subjected to registration in value-added tax and have the audited financial reports for two years from 2024 and 2025. In this study, the Hausman test was applied and found that the fixed effect model is appropriate for analysis. The findings demonstrate that increased income tax, value-added tax, and presumptive tax impose a greater burden on SMEs, which in turn negatively affects the growth of the SMEs. SMEs that pay taxes regularly often exhibit low after-tax Profit. In contrast, firms that regard tax compliance as a significant factor can mitigate the adverse effects of taxation. This finding provides implications for governments to improve taxpayer services and streamline timely payments by alleviating the tax burden associated with SMEs. This research contributes to the literature on tax policy and SMEs studies for developing countries. These results provide insights for policymakers to enhance economic growth and corporate development in low-income nations to improve employability rates.